PENGARUH APLIKASI GOOGLE CLASSROOM TERHADAP MINAT BELAJAR SISWA SMA/SMK - Sri Arum; Yoga Budi Bhakti (UNIVERSITAS INDRAPRASTA PGRI, 2020)
This study aims to determine the effect of alternative learning media Google Classroom on student learning interest as a learning media bridge in the co-19 pandemic situation. Is this application can increase student interest in learning. It is feared that with the spread of Covid-19 student interest in learning will decline and carry out boring distance learning activities because the assignment and provision of material is not varied and effective. From the results of the survey by giving a questionnaire statement via google form conducted on high school students (high school) or equivalent to determine student responses to learning media. The results of student responses obtained an average value of agreeable presentation of 63.9% and 36.1% disagree, including the category of